Knowledge sources and images of innovation in micro and small-sized tourism enterprises: travel agencies and hotels in Bogotá and Pereira (2017)
The aim of this paper is to identify the sources of knowledge to entrepreneurs attending the tourism sector and establish whether the sources are used as a basis to generate innovation. Semi-structured interviews to six hotel managers and nine travel agencies from the tourism sector in the cities of Bogota and Pereira were made. The results show that employers turn to their own sources of knowledge, their family and the market, leaving aside the specialized knowledge from research processes and / or from regional or national institutions order. It is also appreciated that the images that they have been built about innovation are related to dimensions such as differentiating practices, novelty or improvement, implementation of technological tools and validation of innovation by the market. It is concluded that the limited use of sources fails to modify the resource base substantially, therefore,  this  makes it  difficult to generate innovation.